Sinamot Tradition in Traditional Toba Batak Weddings - Deviara Lestari; Tiarnita Maria Sarjani Siregar; Adel Pinola Br Ginting; Jose Christian; Nurfarah Nurfarah (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
Marriage holds great significance for the Batak community, which follows the traditional Dalihan Na Tolu system. In the Toba Batak tribe, a gift called Sinamot is given as a tribute to the bride-to-be's family. The research conducted for this study utilized various data collection methods from relevant and up-to-date journal sources. The findings of the study suggest that the Sinamot tradition within the Toba Batak tribe serves as a means to reinforce the connection between two kinship groups. This tradition is a necessary condition for the legitimacy of marriage under the custom and involves various objects and stages. This event is marked by the presence of various objects that hold significant meaning, such as goldfish, meat, money, and ulos cloth. The preparation process involves various stages, including Marhori-hori walls and Marhusip, which are designed to ensure the continuity and success of the event. The implementation of Sinamot requires careful planning and discussion from both the bride and groom's families, and it is viewed as a way to pay tribute to traditional Batak kings and their families. Ultimately, Sinamot is a symbol of respect for Batak culture and traditional family values.